Assessing the effectiveness and the feasibility of a group-based treatment for self-stigma in people with mental disorders in routine mental health services in North-East Italy: study protocol for a pragmatic multisite randomized controlled trial - Antonio Lasalvia; Luca Bodini; Doriana Cristofalo; Veronica Fin; Philip T. Yanos; Chiara Bonetto (Trials)
Abstract Background Self-stigma refers to the process whereby individuals with mental disorders internalize negative societal attitudes and misconceptions about mental health conditions, potentially affecting their sense of self-worth and identity. This internalization can significantly impact various aspects of life, including treatment engagement, personal relationships, and overall well-being. Narrative Enhancement and Cognitive Therapy (NECT) was developed in the United States to counteract self-stigma and has been supported by multiple randomized controlled trials. However, NECT has not yet been implemented in Italy or within a public mental health system grounded in community psychiatry. This study aims to evaluate the efficacy and feasibility of the Italian version of the NECT within the public mental health sector in a large part of North-East Italy. Methods and analysis This pragmatic, multisite, superiority, randomized, wait-list controlled trial with two parallel arms will recruit over four hundred patients with severe mental disorders from 26 public community-based mental health centers in North-East Italy. The experimental intervention, NECT, consists of 20 group-based sessions to reduce self-stigma. The study will assess NECT’s impact on several psychological dimensions, including self-stigma levels (primary outcome), self-esteem, hope, empowerment, recovery perception, mental well-being, and stigma stress (secondary outcomes). Feasibility will be evaluated by collecting data on participant adherence and treatment implementation, including eligibility screening, participation rates, intervention completion, exposure levels, and reasons for dropout. Discussion The findings of this research are expected to contribute to the understanding of effective treatments for patients with mental disorders, particularly those burdened by high levels of self-stigma, and to improve their recovery outcomes. Trial registration ClinicalTrials.gov; Identifier: NCT06567145.